(L,M)-Fuzzy σ-Algebras - Fu-Gui Shi (International Journal of Mathematics and Mathematical Sciences)
The notion of (L,M)-fuzzy σ-algebras is introduced in the lattice value fuzzy set theory. It is a generalization of Klement's fuzzy σ-algebras. In our definition of (L,M)-fuzzy σ-algebras, each L-fuzzy subset can be regarded as an L-measurable set to some degree.